The curious case of biliary emesis and bowel obstruction from Bouveret syndrome. Issue 8 (28th August 2019) - Chow, Bing Lun; Zia, Khawaja; Scott, Stuart; Pathmarajah, Mariasoosai
Abstract : Bouveret syndrome is a rare complication of biliary lithiasis. This sequela is caused by the passage of the gallstone via a bilioenteric fistula, resulting in an impacted gallstone in the duodenum or stomach. The common presentation of non-specific symptoms contributes to the diagnostic uncertainty and delay, which is strongly associated with adverse outcomes. We report an uncomplicated stone extraction via open gastrotomy in an elderly man afflicted with bowel obstruction and biliary vomit secondary to Bouveret syndrome.